2020
DOI: 10.1016/j.eclinm.2020.100560
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of comprehensive smoke-free legislation on neonatal and infant mortality in Thailand using the synthetic control method

Abstract: Background Almost all of the evidence on the benefits of smoke-free legislation on child health comes from evaluations in high-income countries. We investigated the effects of Thailand's 2010 comprehensive smoke-free legislation on neonatal and infant mortality. Methods To overcome some of the methodological issues inherent to traditional quasi-experimental methods, we applied the novel synthetic control approach. Using 2001–2017 country-level panel data from the World … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
(76 reference statements)
0
7
2
Order By: Relevance
“…Future research could build on our findings by assessing the impacts of the other MPO-WER measures across multiple countries. Previous evidence is limited by the fact that it is based on country or regional level case studies, limiting external validity [10,31,43,44]. While our current study did include information about other MPOWER policies as covariates, these should not be interpreted causally since the choice of models and covariates was driven by the need to adjust for potential confounders associated with taxation and child survival outcomes specifically.…”
Section: Plos Global Public Healthmentioning
confidence: 94%
See 1 more Smart Citation
“…Future research could build on our findings by assessing the impacts of the other MPO-WER measures across multiple countries. Previous evidence is limited by the fact that it is based on country or regional level case studies, limiting external validity [10,31,43,44]. While our current study did include information about other MPOWER policies as covariates, these should not be interpreted causally since the choice of models and covariates was driven by the need to adjust for potential confounders associated with taxation and child survival outcomes specifically.…”
Section: Plos Global Public Healthmentioning
confidence: 94%
“…Covariates were selected based on their previously demonstrated impact on the outcomes and exposure variables [13,31]. All models were adjusted for Gross Domestic Product (GDP) per capita, fertility rate, and MPOWER tobacco control measures (excluding 'Raise taxes', as we analysed detailed taxation data, and scores for 'Monitoring of tobacco use', as this measure is not expected to have an impact on the outcomes).…”
Section: Covariatesmentioning
confidence: 99%
“…12 Evidence also suggests that implementing comprehensive smokefree legislation is associated with reduced neonatal mortality and infant mortality. [12][13][14][15] Previous evidence is, however, predominantly derived from studies in HICs and cannot be directly generalised to lowincome and middleincome countries (LMICs), because of their different economic, social, and environmental backgrounds, higher rates of neonatal and infant deaths, and often weaker implementation of smokefree legislation. 12,16 The influence of the tobacco industry and the awareness of the TSErelated harms is considerably less favourable in LMICs than in HICs, which might hinder the success of tobaccocontrol policies.…”
Section: Introductionmentioning
confidence: 99%
“…22,25 Three studies have evaluated the effects of smokefree legislation on child health outcomes in middleincome countries (MICs), in Brazil, Peru, and Thailand. 14,15,26 Although these studies also showed the positive effects of smokefree legislation, they were conducted in countries known to be tobaccocontrol leaders and with a higher gross domestic product (GDP) per capita than many other MICs. 11 Thus, it is unclear whether the child health benefits of comprehensive smokefree legislation identified in these studies are generalisable to all 106 World Bank MICs.…”
Section: Introductionmentioning
confidence: 99%
“…The only application of SCM relating to malaria is by Barofsky et al (2015) who evaluate the long-term economic consequences (schooling and employment) of the 1959-1960 malaria eradication campaign in Uganda. We are aware of only two applications of SCM in public health; an evaluation of a smoke free legislation in Thailand on neonatal and infant mortality (Radó et al, 2020) and the impact of a decline in country democratic traits on universal health coverage (Wigley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%